Under pressure: Investigating marine resource-based livelihoods in Jakarta Bay and the Thousand Islands. Issue 2 (30th September 2016) - Baum, Gunilla; Kusumanti, Ima; Breckwoldt, Annette; Ferse, Sebastian C.A.; Glaser, Marion; Dwiyitno,; Adrianto, Luky; van der Wulp, Simon; Kunzmann, Andreas
Abstract: Jakarta Bay, next to the Jakarta Metropolitan Area with around 30 million inhabitants, is facing extreme pollution. Although local coral reefs are degraded and marine resources heavily exploited, they provide livelihoods for millions of people. This study investigates anthropogenic pressures on local fisheries resources and associated livelihoods. Questionnaire surveys were conducted in 15 coastal communities (10 coastal neighborhoods in Jakarta Bay on the mainland and 5 of the offshore Thousand Islands). The most economically valuable species were Caesio cuning (Redbelly yellowtail fusilier) on the islands and Rastrelliger kanagurta (Indian mackerel) on the mainland. Over 80% of all interviewed fishermen regarded the current state of marine resources as declining, mainly due to pollution and overexploitation. While perceptions of declining resources were equally high on the islands and the mainland, pollution was listed as the principal cause of degradation significantly more on the mainland. Findings are discussed in the context of coastal livelihood vulnerability. Highlights: Marine resources are highly exploited inside and outside Jakarta Bay. Local fishermen see pollution and over-exploitation as main drivers for reef degradation. In both areas, local livelihoods strongly depend on the heavily exploited fisheries resources. Fishermen on the mainland tend to have less alternative livelihood options than island residents. Dependency on vanishing fisheries resources is thus larger and vulnerability higher for mainland fishermen.